Developing of Human Resources in E-learning and Practical Experience in its implementation - Gogoladze, Tamar; Zhozhuashvili, Natia; Khojevanishvili, Elene; Tsiklauri, Ana (Discoveries in Agriculture and Food Sciences, 2015)
The article deals with practical experience in developing and implementing human resources in E-learning in Gori State teaching University. German International cooperation civil organization (GIZ) contributed greatly the development of electronic learning sphere during a 7-year cooperation with Georgia. The working groups sent from Gori State teaching University after completion the full course of trainings and getting certificates initiated implementing the project “The Development of Human Recourses for implementation of E-learning” and planned to hold various activities within the project, also the research for finding out the readiness for implementing the innovation was held. The results got by the feedback clarified that the professors and teachers of the University share the necessity of implementing e-learning in the teaching process as an assisting tool and express their readiness for preparation pilot programs. After competition of the full training course (4 modules) the y presented presentations in 10 different disciplines which were greatly approved by GIZ experts. The project participants and leaders made further plans for implementation and development of E-learning. For the country like Georgia, it is important to raise the competences and skills of professors and teachers and mobilize all the resources to meet the challenges of the epoch.